Micro-costing analysis of a community-based psychiatric intervention among people who inject drugs in Haiphong, Vietnam - Trouiller, Philippe; Le, Sao Mai; Hoang Thi, Giang; Duong Thi, Huong; Khuat Thi Hai, Oanh; Nham Thi, Tuyet Thanh; Moles, Jean-Pierre; Laureillard, Didier; Des Jarlais, Don C.; Nagot, Nicolas; Michel, Laurent; Pelletier-Fleury, Nathalie (Frontiers in Psychiatry, 2025)
IntroductionCommunity-based interventions and peer-support have been shown to improve health outcomes and are increasingly promoted in mental health care. To guide further policy makers, we aimed to estimate, from a societal perspective, the cost of a community based psychiatric intervention for people who inject drugs (PWID).MethodsFrom March 2022 to May 2022 in Hai Phong, Vietnam, PWID currently or previously diagnosed with a psychiatric disorder were recruited in a 12 months follow-up cohort and received psychiatric and harm-reduction services supported by peers (Drive-Mind 2 cohort study, NCT05886504). Using a micro-costing approach, we estimated the annual per-participant cost for screening PWID for psychiatric disorders, and for providing them for follow-up care and medicine.FindingsAll 563 participants who were enrolled in Drive-Mind-2 were screened for psychiatric disorder, and 185 of them were included in a psychiatric follow-up. The total cost of the psychiatric intervention was estimated at $88.7 per participant per year. Recurring goods and services represented 44% of total costs (including medication and transport allowance) and human resources represented 37%. The cost of one screening visit was estimated at $9.8 per participant.ConclusionsCosts for a community-based psychiatric intervention were very low in our study. This data can be used by policy makers in Vietnam to improve a mental health system that is poorly developed and expensive for the patient.